LOCAL CULTURE-BASED COMMUNITY DEVELOPMENT IN SUBANG REGENCY, WEST JAVA - Huraerah, Abu; Nurwulan, Riany Laila; Voo, Peter (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2023)
Abstract. The purpose of this study are to describe the elements that influence local culture and local culture that supports community development at Banceuy, Sanca Village, Ciater District, Subang Regency, West Java Province. This study uses a qualitative descriptive research method with a case study approach. Primary data collection techniques include interviews, observation, document study and focus group discussions. Meanwhile, secondary data sources were obtained through searching various references such as books and journals. The informant selection technique was carried out through purposive sampling. The validity of the data using triangulation of sources and data analysis techniques through data reduction, data display and conclusion/verification. In detail, data analysis uses the coding manual consists of open coding, axial coding, and selective coding. The main factors influencing local culture at Banceuy, Sanca Village, Ciater District, Subang Regency, West Java Province are geography, natural charm, history, and economy. Meanwhile, the local culture for community development are ritual, art, environmental tourism, mutual cooperation, and cultural tourism. Local culture can be a driving force in community development and should be considered in making development policies in the region. Local culture is a community cultural heritage that can support the community's economy. Local culture can be used as a participatory approach in community development. Keywords: Model, local cultur, community development. Abstrak. Tujuan penelitian ini adalah untuk mendeskripsikan unsur-unsur yang mempengaruhi budaya lokal dan mendeskripsikan budaya lokal yang mendukung pengembangan masyarakat di Banceuy, Desa Sanca, Kecamatan Ciater, Kabupaten Subang, Provinsi Jawa Barat. Penelitian ini menggunakan metode penelitian deskriptif kualitatif dengan pendekatan studi kasus. Teknik pengumpulan data primer meliputi wawancara, observasi, studi dokumen dan diskusi kelompok terarah. Sementara, sumber data sekunder diperoleh dengan mencari berbagai referensi seperti buku dan jurnal. Teknik pemilihan informan dilakukan melalui purposive sampling. Validitas datas menggunakan triangulasi sumber dan teknik analisis data melalui reduksi data, display data dan penarikan kesimpulan/verifikasi. Secara rinci, analisis data menggunakan koding secara manual, yaitu open coding, axial coding dan selective coding. Faktor utama yang mempengaruhi budaya lokal di Banceuy, Desa Sanca, Kecamatan Ciater, Kabupaten Subang, Provinsi Jawa Barat adalah geografi, pesona alam, sejarah dan ekonomi. Sementara, budaya lokal untuk pengembangan masyarakat adalah ritual, kesenian, wisata lingkungan, gotong-royong dan wisata budaya. Budaya lokal dapat menjadi pendorong dalam pengembangan masyarakat dan hendaknya menjadi pertimbangan dalam pembuatan kebijakan pembangunan di daerah. Budaya lokal merupakan warisan budaya masyarakat yang dapat menunjang ekonomi masyarakat. Budaya lokal dapat digunakan sebagai pendekatan partisipatif dalam pengembangan masyarakat. Kata kunci: model, budaya lokal, pengembangan masyarakat.